Wild beans (Phaseolus vulgaris L.) reaction to planting depth - Peña-Valdivia, Cecilia B.; Trejo, Carlos; Celis-Velazquez, Raquel; López Ordáz, Anselmo (Revista Mexicana de Ciencias Agrícolas, 2018)
Populations of wild beans (Phaseolus vulgaris L.) are currently used by humans incipiently; many of which are tolerant to environmental stress inducers and their nutritional traits and exceptional quality can therefore represent an untapped resource. The aim of the study was to describe the reaction of wild beans planting depth and contrast it with that of cultivars. The hypothesis was that, as in the wild, wild bean ́s seeds germinate near the soil surface where they are deposited after spontaneous dehiscence of pods as planting depth negatively affects seedling emergence. We used a completely randomized design with factorial arrangement of treatments (15 x 4) under greenhouse conditions. The factors studied were: plant material (six wild genotypes, three traditional cultivars and six improved cultivars) and planting depth (2.5, 5, 7.5 and 10 cm). We also evaluated seed biomass, time for starting and ending the emergence (total or maximum), and emergence percentage initial and maximum. The cumulative emergence wild beans showed logistic trend (y= k/l + [k-n/ne-rx]) as domesticated. Wild beans depth of 2.5 and 10 cm took 1 d more (p≤ 0.05) for the emergency start (7.67 and 9.93 d) compared with the domesticated (6.43 and 2.9 d), but the initial emergence percentage was not different at all (p> 0.05). The maximum emergence was different (p≤ 0.05) by only 10 cm, in which wild beans emerged in a higher proportion (72.78%) than domesticated (59.02%). Planting depth is no disadvantage to the emergence of wild beans.
Keywords: domestication; seedling; natural resources